SURVEY OF PB LAUSER ATHLETES' SMASH ABILITIES IN CENTRAL ACEH - Maulana, Hairil; Munzir, Munzir; Yudha Pranata, Didi (Universitas Negeri Medan, 2023)
Badminton is one of the most popular in Indonesia and the world. The game of badminton has basic techniques such as serves and smashes. Smash in badminton is a technique that is very necessary to get a point. This research aims to determine the smash ability of Central Aceh PB Lauser athletes. This type of research is quantitative descriptive research. The sample for this research was 5 athletes in the Men's Singles category PB Lauser Central Aceh. The research results from the five athletes had a maximum score of 35, a minimum score of 25, a mean of 29.2, and a standard deviation of 4.33. The good category is 40% and the bad category is 60%, so it can be concluded that the abilities of PB Lauser Aceh athletes are in the medium category. It is a good suggestion for the coach to provide a training program that leads to smash ability in badminton, such as training arm muscle strength.